About the Short Internet Forms Encouraging to Click - Ławecka, Izabella (Media - Culture - Social Communication, 2019)
The aim of the author of this paper is to presents short Internet forms encouraging Internet users to click. These forms could be an announcement, to lead to more expanded texts or online usage forms; also to invite participation in the media, e.g. newsletter subscriptions, registration forms and texts leading to a profile on social media. The paper analyses language treatments and how they affect receiver reactions.